2021
DOI: 10.1007/s11192-021-04167-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and characterizing social media communities: a socio-semantic network approach to altmetrics

Abstract: Altmetric indicators allow exploring and profiling individuals who discuss and share scientific literature in social media. But it is still a challenge to identify and characterize communities based on the research topics in which they are interested as social and geographic proximity also influence interactions. This paper proposes a new method which profiles social media users based on their interest on research topics using altmetric data. Social media users are clustered based on the topics related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
0
10
0
1
Order By: Relevance
“…A Q value of at least 0.3 implies meaningful clustering [ 44 ]. The result of clustering, and consequently Q, was significantly determined by the preselected resolution [ 46 ]. Following an iterative process, we aimed to find a proper balance between the number and relevance of the discovered communities and the resulting modularity by applying different resolution values [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Q value of at least 0.3 implies meaningful clustering [ 44 ]. The result of clustering, and consequently Q, was significantly determined by the preselected resolution [ 46 ]. Following an iterative process, we aimed to find a proper balance between the number and relevance of the discovered communities and the resulting modularity by applying different resolution values [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The result of clustering, and consequently Q, was significantly determined by the preselected resolution [ 46 ]. Following an iterative process, we aimed to find a proper balance between the number and relevance of the discovered communities and the resulting modularity by applying different resolution values [ 46 ]. To analyze the most important substances in the network, we calculated the degree centrality (number of linkages of a node) [ 47 ]; the higher the centrality, the more important the substance is in the network [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of important words is a key measure in a bibliometric analysis. If two words frequently appear together, a visible semantic relationship can be observed between them, which is why a higher co-occurrence of two words suggests a more obvious visual similarity between the two (Liu et al, 2012; Arroyo-Machado et al, 2021; Obreja, 2022). Like co-citation of authors and journals, co-occurrence of keywords is a suitable method to emphasize the relationship between two or more concepts.…”
Section: Social Media and Its Embedded Politicsmentioning
confidence: 99%
“…Furthermore, different proposals have been developed to understand how these new publications are shared and discussed in different social media through "altmetrics" (Priem, 2014). These social media metrics have proven useful for understanding aspects of science communication beyond traditional channels (Arroyo-Machado et al, 2021). Regarding COVID-19-related research, Kousha and Thelwall (2020) studied the altmetric impact of COVID-19 publications on different social media platforms and found that early altmetric mentions such as tweets reflect a positive relationship with later citations.…”
Section: Introductionmentioning
confidence: 99%